EXPLORING THE ROLE OF NANOTECHNOLOGY IN DRUG DELIVERY SYSTEMS: PUBLIC HEALTH IMPLICATIONS - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study investigates effectiveness of nanotechnology-based drug delivery systems such as liposomes, polymeric micelles and lipid nanoparticles is investigated in this study. Each nanocarrier's encapsulation efficiency, drug loading capacity, release kinetics and cytotoxicity were assessed using an experimental research design. The highest encapsulation efficiency (92% ± 1.5) and drug loading capacity were shown by polymeric micelles, which are suitable for sustained drug release applications. Polymeric micelles showed controlled release over 24 hours with 85% cumulative drug release, while liposomes and lipid nanoparticles showed faster release rates. Dynamic Light Scattering (DLS) analysis revealed that polymeric micelles had the smallest particle size (110 nm) and moderate zeta potential (+22 mV), indicating their stability and dispersity. High biocompatibility of polymeric micelles was demonstrated in cytotoxicity tests on HeLa cells, where cell viability was 94.3% at 24 hours. Significant differences among the nanocarriers were confirmed by statistical analysis. These results indicate that polymeric micelles are the most promising characteristics for efficient and sustained drug delivery, and thus represent a basis for further development in clinical.